WORLD OIL PRICE FORECAST ON BASIS OF EXPERT NON-NUMERIC KNOWLEDGE - Yu. A. Nazarova (Финансы: теория и практика)
This work is devoted to the compilation of aggregate forecast of world oil prices by the Aggregated Indices Randomization Method (AIRM). This method allows conducting the multicriteria evaluation of complex economic and financial indicators on basis of non-numeric, non-exact and non-complete expert information. It assumes an estimation the probability of alternative development options based on the ordinal and interval information by double randomization of alternatives’ probabilities, and weight coefficient, which takes into account the importance of the source of the forecast.As a source of expert information we have taken the Ministry of Economic Development of Russia, the European Commission, the Energy Information Administration US Department of Energy, Barclays Commodities Research reports and statements of experts of international rating agency Fitch Ratings regarding the average price for Brent crude oil for 2015. As the weighting coefficients we have taken the degree of compliance of analysts’ forecasts for 2013 to reality calculated based on the error variance.The result of the study is to determine the probabilities of each of the alternative outcomes and to identify the most likely range of prices for Brent crude oil for 2015. The resulting consolidated assessment can be used to make management and investment decisions and also as a basis for forecasting other economic indicators that depend on world oil prices, including oil and gas revenues. Also, a forecast gives the opportunity to adjust already compiled forecast by the Ministry of economic development for 2015.